2013
DOI: 10.1002/ls.1246
|View full text |Cite
|
Sign up to set email alerts
|

Coupled couple stress and surface roughness effects on elasto-hydrodynamic contact

Abstract: This paper deals with the combined effects of couple stress and surface roughness to inspect the elasto‐hydrodynamic performance of slider bearing systems. On the basis of the couple stress Stokes theory and homogenisation method, the homogenised generalised Reynolds equation including the slider bearing stationary surface deformation is derived. The total deformation include the deformation of smooth surface, taken into account by the elastic thin layer model, and the deformation of roughness corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…They are obtained for different values of the elastic thin layer thickness d (compliance coefficient C s ) such as titanium alloy material. With the aim to validate the present computer program, both load capacity W * and friction coefficient C f are given in Tables I and II to compare with Nabhani et al (2014) in the case of deformable bearing for different given values of couple stress parameter l *. In addition, the dimensionless load capacity W * of infinitely wide slider-bearing is displayed in Table III for comparison with Lin et al (2009) and Nabhani and El Khlifi (2015) for different given values of Hartmann number M in the case of Newtonian lubricant ( l * = 0).…”
Section: Resultsmentioning
confidence: 99%
“…They are obtained for different values of the elastic thin layer thickness d (compliance coefficient C s ) such as titanium alloy material. With the aim to validate the present computer program, both load capacity W * and friction coefficient C f are given in Tables I and II to compare with Nabhani et al (2014) in the case of deformable bearing for different given values of couple stress parameter l *. In addition, the dimensionless load capacity W * of infinitely wide slider-bearing is displayed in Table III for comparison with Lin et al (2009) and Nabhani and El Khlifi (2015) for different given values of Hartmann number M in the case of Newtonian lubricant ( l * = 0).…”
Section: Resultsmentioning
confidence: 99%
“…Considering couple stress effect of journal with a smooth surface, the modified Reynolds equations of hydrodynamic lubrication [26] was given as:…”
Section: Average Reynolds Equation Of Couple Stress Fluidmentioning
confidence: 99%
“…Moreover, the couple stress parameter decreased obviously as the viscosity-pressure effect was considered. Based on Christensen stochastic theory, Nabhani M, 26 Naduvinamani 27 and Hanumagowda 28 derived the Reynolds equation of stochastic MHD couple stress. Transverse roughness supported larger dynamic stiffness, carrying capacity, and damping coefficients than smooth surfaces, while longitudinal roughness had the opposite effects.…”
Section: Introductionmentioning
confidence: 99%
“…The load-carrying capacity and the coefficient of friction were enhanced due to the existence of such protrusions. The combined effect of surface roughness and couple stress fluid on the elastohydrodynamic performance of journal bearing was studied by Chiang et al [22] and Nabhani et al [23]. It was observed that the interaction between couple stress, surface roughness and elastic deformation effects is significant.…”
Section: Introductionmentioning
confidence: 99%